The Role of Leadership Function as A Mediating Variable Between Leadership Behaviour and Organizational Performance - Stefanie Maria Natasha Nugroho; Niluh Putu Dian Rosalina Handayani Narsa (Jurnal Akuntansi dan Keuangan, 2023)
This study examined the relationship between leadership behaviour and organizational performance and the relationship between leadership behaviour and leadership functions. It also analyzed the relationship between leadership functions and organizational performance and the relationship between leadership behaviour and organizational performance using leadership functions as mediating variables. The research data was obtained from 282 state apparatus staff from Surabaya's 62 Regional Working Unit Organizations. The results of this study identified a positive relationship between leadership behaviour and organizational performance, as well as demonstrated that leadership functions can partially mediate the relationship between leadership behaviour and organizational performance. This research is expected to provide insight to leaders in the Regional Working Unit Organization on the importance of good behaviour and leadership functions in leading the organization to achieve better performance.